Design and analysis of a rear diffuser in a sedan car. (2022) - Senthilkumar, P.B.; Parthasarathy, M.; Aravind, L.; Narayanan, R.G. Satthya; Vegesh, B.; Sam Nelson, D.R.
Abstract: The aerodynamic characteristics have a great influence on the fuel economics and the steering stability of a high-speed vehicle. Thus, this aerodynamics is considered as one of the main ergonomics of the vehicle. Aerodynamics consists of four forces which an object or material moves. The forces are lift, drag, weight, thrust. From these four forces lift and drag plays a major role in the vehicle which runs on the road surface. To maintain steady aerodynamics various add-on devices, help in maintaining the forces that act on the vehicle. The add-on devices are spoilers, rear wing, tail plates, vortex generator, and diffuser. From these add-on devices, we take a diffuser for our project and make a design and analyze and compare it with the existing diffuser. Usually, the diffuser is first implemented in the racing field then it gradually came to use in commercial vehicles. As time moves on the people and automotive industry focuses on the efficiency of the vehicle. The main aspect to provide the best efficiency is aerodynamics. So, the add-on devices are added to the vehicle to provide the best efficiency. A modified diffuser is designed based on the aspects of the car model. By modeling these three designs using CATIA we are going to analyze them using ANSYS. In that, using CFD (Computational Fluid Dynamics) which specializes in the flow of air and water. Analyze the drag and lift coefficient based on the velocity and the different diffusers. The expected outcome of the project work is to reduce the drag and lift coefficient compared to the existing diffuser. This project deals with the design and analysis of the car model without a diffuser, with an existing diffuser, and with a modified diffuser which results in the comparison of their values.